Transformations of Diatom-Derived Dissolved Organic Matter by Bacillus pumilus Under Warming and Acidification Conditions - Liu, Yang; Wang, Xueru; Sun, Jun (Frontiers in Microbiology, 2022)
Heterotrophic bacteria are assumed to play an important role in processing of phytoplankton-derived dissolved organic matter (DOM). Although the algae-derived organic matter is commonly studied, the transformation and processing of DOM by epiphytic bacteria for phytoplankton have rarely been investigated, especially under warming and acidification. In this study, Bacillus pumilus is used to explore the ecologically important marine diatom Skeletonema dohrnii-derived DOM under different conditions (temperature, 27°C and 31°C; pCO2, 400 and 1,000 ppm), utilizing fluorescence excitation-emission matrix (EEM) combined with parallel factor analysis (EEM-PARAFAC). Fluorescence regional integration and the peak selecting method are used to generate B, T, N, A, M, and C peaks in the EEM fluorescence spectroscopy. The main known fluorophores including that protein-like components (peaks B and T), unknown components (peak N), and humic-like component (peaks A, M, and C). Our experimental results showed that under higher temperature and pressure of CO2 (pCO2) conditions, S. dohrnii-derived DOM fluorescence was dominated by a protein-like signal that slower waning throughout the experiment, becoming an increasingly humic-like substance, implying that processing by the epiphytic bacteria (B. pumilus) produced more complex molecules. In addition, spectroscopic indices (e.g., fluorescence index, biological index, freshness index β/α, and humification index) were changed in varying degrees. This study reveals and confirms the direct participation of heterotrophic bacteria in the transformation and generation of algae-derived DOM in the laboratory, underlining the influence of global warming and ocean acidification on this process.